Carbon and nitrogen stable isotope ratios of particulate organic matter in the southern Sea of Japan from 2018 to 2021 - Kodama, Taketoshi; Nishimoto, Atsushi; Nakamura, Ken-ichi; Nakae, Misato; Iguchi, Naoki; Igeta, Yosuke; Kogure, Yoichi (PANGAEA, 2023)
Carbon and nitrogen stable isotope ratio of particulate organic matter (POM) was collected in the surface layer of the southern Sea of Japan. 0.9–11.5 L of seawater was filtered using a pre-combusted (450 °C, 6 h) glass fiber filter (GF/F, Whatman), and the carbon and nitrogen isotopic ratios were measured using an Isoprime 100 isotopic ratio mass spectrometer (Elementar, Langenselbold, Germany). The carbon: nitrogen ratio (C: N ratio) of POM occasionally showed outlier values. Therefore, the means and standard deviations (SDs) of the C: N ratio were calculated, and samples whose C: N ratio differed by > 3 × SD from the mean value were eliminated. With the POM, temperature, salinity, chlorophyll a concentration, and nutrient concentrations were measured.
Keywords: carbon isotope; isotope ratios; nitrogen isotope; Sea of Japan